c) Hence, or otherwise, evaluate : \( \begin{aligned}\left(\frac{1}{4}+\frac{3}{4}\right) & +\left(\frac{1}{6}+\frac{3}{6}+\frac{5}{6}\right)+\left(\frac{1}{8}+\frac{3}{8}+\frac{5}{8}+\frac{7}{8}\right)+\cdots+\left(\frac{1}{50}+\frac{3}{50}+\frac{5}{50}+\cdots\right. \\ & \left.+\frac{49}{50}\right)\end{aligned} \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
The Deep Dive
To evaluate the given expression, we can first observe the pattern in each grouping of fractions. Starting with the first group: \[ \frac{1}{4} + \frac{3}{4} = \frac{4}{4} = 1. \] For the second group: \[ \frac{1}{6} + \frac{3}{6} + \frac{5}{6} = \frac{1+3+5}{6} = \frac{9}{6} = 1.5. \] For the third group: \[ \frac{1}{8} + \frac{3}{8} + \frac{5}{8} + \frac{7}{8} = \frac{1+3+5+7}{8} = \frac{16}{8} = 2. \] More generally, we note that the nth term groups sum the first n odd numbers divided by \( n \): \[ S_n = \sum_{k=1}^{n} (2k-1) = n^2. \] Thus, we can conclude that: \[ \frac{1 + 3 + 5 + \cdots + (2n-1)}{2n} = \frac{n^2}{2n} = \frac{n}{2}. \] Now, our expression consists of groups from \( n = 2 \) to \( n = 25 \): \[ 1 + 1.5 + 2 + 2.5 + \cdots + 12.5. \] This is an arithmetic series with: - First term \( a = 1 \), - Last term \( l = 12.5 \), - Number of terms \( n = 25 - 2 + 1 = 24 \). To find the sum \( S \) of an arithmetic series: \[ S = \frac{n}{2}(a + l) = \frac{24}{2}(1 + 12.5) = 12 \times 13.5 = 162. \] Thus, the final value of the original expression is: \[ \boxed{162}. \]